PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA ATAS PERJANJIAN HUTANG PIUTANG TERKAIT WANPRESTASI YANG DILAKUKAN OLEH KONSUMEN PADA UD BHUANA RAHAYU - Suryawan, I Putu Agus Krisna; Sugiantari, Anak Agung Putu Wiwik (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
The debt and receivable agreement entered into by business actors and consumers at UD Bhuana Rahayu is a money lending and borrowing agreement. The contents of the agreement must be implemented by the parties, especially consumers, by returning the debt in accordance with Article 1754 of the Civil Code. Apart from that, this is done to fulfill consumer obligations and the rights of business actors. However, in reality there are consumers who do not pay their debts (default) which results in losses for business actors. So the procedures and mechanisms for resolving defaults are being questioned, as well as how legal protection can be provided to business actors. Through empirical legal research methodology, the answer was obtained that business actors use verbal/unwritten agreements in debt and receivable agreements. The solution can only be resolved through mediation. Therefore, the legal protection that can be provided is repressive legal protection through statutory regulations that have been regulated to prevent, and preventive legal protection through resolving litigation, namely district court lawsuits.